Non-Mandatory Economic Instruments for Conservation: An Outlook on their Emergence and Evolution in Mexico - Rodriguez , Karla Juliana; Ávila Foucat, Sophie (Sociedad y Economía, 2013)
Environmental policy in Mexico has been based on non-mandatory economic instrumentssuch as Forest Management Certification (FC) and Payment for Environmental Services (PES)as a strategy to advance in natural resources conservation. The analysis of the evolution ofthese public policy instruments allows understanding the context in which they were designedand implemented, which is useful to redesign or evaluate them. Thus, this articlepresents an analysis of the emergence, evolution and current trends after two decades of FCand one decade of PES creation. The semi-structured interviews show that although internationalpolicies have been one of the most important causes for the emergence of these instruments,their evolution and tendencies have been relatively well consolidated through nationalpublic policy. The main challenges ahead are to strengthen trade policies (in the caseof FC) and to overcome the discussion between efficiency and equity (in the case of PES).